THE IMPACT OF EIGHTH GRADERS’ SELF-REPORTED METACOGNITIVE READING STRATEGIES ON 2019 NAEP INFORMATIONAL READING SCORES - Menko, Katie; Zhang, Mingyuan (International Journal of Research -GRANTHAALAYAH, 2023)
This study presented a secondary analysis of the National Assessment of Educational Progress (NAEP) dataset. It examined the impact of eighth graders’ self-reported metacognitive reading strategies on their 2019 NAEP informational reading scores. A quantitative descriptive research design was utilized to analyze secondary data extracted from the 2019 NAEP dataset. The findings are: (1) The average subscale score of students who feel that they definitely can recognize when they don’t understand something they are reading is significantly higher than those who reported a lower ability level. (2) The average subscale score of students who feel that they definitely can figure out the meaning of a word they don’t know by using other words in the text is significantly higher than those who reported a lower ability level. (3) The average subscale score of students who feel that they definitely can identify the main idea of a text is significantly higher than those who reported a lower ability level. These findings indicate that metacognitive reading strategy instruction could be beneficial to students’ informational reading comprehension, and therefore, the need for further educator professional development on metacognitive reading instruction is warranted.